Storylines About Rural Teachers in the United States: A Narrative Analysis of the Literature - Megan Burton; Kara Brown; Amy Johnson (Journal of Research in Rural Education, 2013)
This narrative literature analysis examines the storylines of rural teachers told through published research on rural teachers. Using a narrative analysis approach, we investigated research published between 1970 and 2010"four decades of ruraloriented education research and policy work. Four storylines emerged from our coding of rural-related education research: (1) rural teachers are professionally isolated, (2) rural teachers are different from urban and/or suburban teachers, (3) rural teachers are often lacking in professional knowledge/teaching credentials, and (4) rural teachers are particularly resistant to change. Examining the explicit and implicit ways in which rural teachers and schools are portrayed as problematic in research underscores the significant role academics play in sustaining the "rural problem" storyline.